Two limit theorems for non-identically distributed summands - Nagayev, A. V.; Hodjabagian, S. S. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. В. Нагаев, С. С. Ходжабагян. Две предельные теоремы для неодинаково распределенных слагаемыхA. V. Nagajevas, S. S. Chodžabagianas. Pora ribinių teoremų nevienodai pasiskirsčiusių dydžių sumoms